Low profile UHF loop antenna prototyped and investigated by circuit modeling. Issue 2 (February 2017) - Taghvaee, H.; Habibi, A.; Rezaee, A.; Zarinkhat, F.
ABSTRACT: Here we proposed a low profile antenna which is an electrically coupled loop fed by a coaxial cable and operates in UHF band. With acquisition of a square loop, near zone is covered by magnetic field that has no harm to living being. By optimizing the dimensions with genetic algorithm 12% of bandwidth, 2.45 dB realized gain and 33% miniaturization ( λ → 2 / 3 λ ) at 500 MHz is obtained. Afterwards, the performance of the antenna is analyzed with a general circuit model and verified using frequency domain solver simulation. In the measurement phase a technique was discovered improving the bandwidth even more, hence 150 MHz bandwidth equal 30% at 500 MHz was achieved. These characteristics together make this antenna very beneficial in mobile terminals that have a very wide area of applications such as ground station targeting UAVs and where antennas need to operate close to the human body. Due to semidirectional radiation pattern it can be used in short and medium range remote wireless bridge networks. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:459–463, 2017